2016
DOI: 10.1080/19415257.2016.1258655
|View full text |Cite
|
Sign up to set email alerts
|

Extending the teacher educator role: developing tools for working with school mentors

Abstract: This article considers the ways a group of university-based teacher educators work with school-based mentors (cooperating teachers). Owing to a number of changes in teacher education policy in England, feelings of marginalisation from the teacher educators are presented before exploring how they undertake their work with school mentors. Using a cultural and historical activity theory lens through which to view interview data, the analysis explores how teacher education activity has changed over the nine years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The tools used as evidence of classroom practices aim to provide pre-service teachers with structured opportunities to reflect upon and possibly rethink their beliefs. This, in turn, allows them to improve their teaching practice (Clarke 1995, Timperley 2001, Cochran-Smith and Lytle 2009, Earl and Timperley 2009, Ure 2010, Kriewaldt and Turnidge 2013, McLean, Davies et al 2013, Douglas 2017. We argue that specific structures and tools are necessary to ensure professional conversations between mentor teachers, university educators and pre-service teachers that are valuable for development.…”
Section: Professional Conversations: Evidence Feedback and Dialoguementioning
confidence: 91%
“…The tools used as evidence of classroom practices aim to provide pre-service teachers with structured opportunities to reflect upon and possibly rethink their beliefs. This, in turn, allows them to improve their teaching practice (Clarke 1995, Timperley 2001, Cochran-Smith and Lytle 2009, Earl and Timperley 2009, Ure 2010, Kriewaldt and Turnidge 2013, McLean, Davies et al 2013, Douglas 2017. We argue that specific structures and tools are necessary to ensure professional conversations between mentor teachers, university educators and pre-service teachers that are valuable for development.…”
Section: Professional Conversations: Evidence Feedback and Dialoguementioning
confidence: 91%
“…The results only provide first evidence for the relationships between opportunities to learn reported by teacher educators, those perceived by pre-service teachers and professional knowledge. Secondly, we have no additional data on the teacher educators, such as their own qualifications and professional development, even though prior research has identified them as a heterogeneous group (Douglas 2017;Swennen et al 2010), which might have affected our results. Third, one should note that the same applied to the pre-service teachers, as we lacked a measure of their initial level of knowledge.…”
Section: Limitationsmentioning
confidence: 99%
“…The liaisons attributed activities such as co-creating, coordinating, and communicating to their role and functioned as boundary-spanners between the PDS schools and the TE (Whitenack & Swanson, 2013). Liaison teams explored their work relationships to serve the teacher candidates and mentor teachers in innovative ways (Douglas, 2017). But the role as a liaison was always added to the work of the coordinator, vice-principal, or resource teacher.…”
Section: Rolesmentioning
confidence: 99%